Non-invasive intracranial pressure monitoring for high-grade gliomas patients treated with radiotherapy: results of the GMaPIC trial - Casile, Mélanie; Thivat, Emilie; Giraudet, Fabrice; Ginzac, Angeline; Molnar, Ioana; Biau, Julian; Brehant, Julien; Lourenco, Blandine; Avan, Paul; Durando, Xavier (Frontiers in Oncology, 2024)
Patients with high-grade gliomas are at risk of developing increased intracranial hypertension (ICHT) in relation to the increase in volume of their tumor. ICP change cannot be measured by invasive method but can be estimated by using routine clinical signs, in combination with a standard imaging method, magnetic resonance imaging (MRI). A non-invasive monitoring of ICP could be of interest in highgrade glioma, in particular after radiotherapy treatment with as major side effect a cerebral oedema.This prospective clinical study aimed to compare the ICP changes (estimated by a non-invasive method based upon distortion product otoacoustic emissions (DPOAE) monitoring) with volume changes observed on MRI in patients with high-grade gliomas treated with radiotherapy. DPOAE measurements were performed one month after the end of radiotherapy and then every 3 months for one year. At each visit, the patient also underwent MRI as well as an evaluation of clinical signs.The variation in the estimate of intracranial pressure readout measured at each follow-up visit (in absolute value with respect to the baseline measurements) was significantly associated with the variation of T2/FLAIR volume (n=125 ; p<0.001) with a cut off value of change ICP readout of 40.2 degrees (e.i. an estimated change of 16 mm Hg).The GMaPIC trial confirm the hypothesis that the ICP change estimated by DPOAEs measurement using a non-invasive medical device is correlated with the change of the tumor or edema in high grade glioma after radiotherapy. The device could thus become an easy-to-use and non-invasive intracranial pressure monitoring tool for these patients.